2013
DOI: 10.1186/1471-2415-13-58
|View full text |Cite
|
Sign up to set email alerts
|

Indapamide-induced transient myopia with supraciliary effusion: case report

Abstract: BackgroundIngestion of sulphonamide-derived drugs has been reported to possibly have ocular side-effects. Authors aimed to present a rare case of indapamide-induced transient myopia with ciliary body edema and supraciliary effusion.Case presentationA 39 years old caucasian female patient presented at the Department of Neurology with headache and sudden bilateral loss of distant vision. Neurological assessment and cranial CT scans were unremarkable. For her hypertension, twice a day bisoprolol 2.5 mg and once a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 8 publications
(15 reference statements)
0
20
0
4
Order By: Relevance
“…Végh et al 5 used ultrasound biomicroscopy (UBM) to observe the morphological changes of the lens and ciliary body in a phakic patient and concluded that both ciliary muscle contraction and ciliary body oedema played a key role. In addition, UBM-based studies3 5 8 11 noted a minor increase of lens thickness but they could not correlate it with either shallowing of AC or myopic shift.…”
Section: Discussionmentioning
confidence: 99%
“…Végh et al 5 used ultrasound biomicroscopy (UBM) to observe the morphological changes of the lens and ciliary body in a phakic patient and concluded that both ciliary muscle contraction and ciliary body oedema played a key role. In addition, UBM-based studies3 5 8 11 noted a minor increase of lens thickness but they could not correlate it with either shallowing of AC or myopic shift.…”
Section: Discussionmentioning
confidence: 99%
“…Mindezek alapján úgy véljük, eseteinket nem annyira az acetazolamid ismert idioszinkráziás hatása ritka, speciális formájának, hanem enyhébb és ezért ritkán felfedezett formájának kellene tartanunk. A szulfonamidok által okozott sugárizom-ödéma viszonylag széles és változa-tos szemészeti hatásspektrumára utalt az a jelen szerzők tollából származó közlemény is, ahol az indapamid okozta átmeneti rövidlátás önmagában, glaucoma kialakulása nélkül jelentkezett [9], valamint az a tény, hogy különböző időpontokban adott egyén is különböző mó-don reagálhat ugyanazon szulfonamidszármazékra [12]. A szóban forgó mellékhatások "tetten érését" az is nehezíti, hogy néha egyszeri dózis is képes azokat kiváltani, míg máskor csak hosszasabb kezelés után alakulnak ki.…”
Section: áBraunclassified
“…Vannak köztük diuretikumok, antidiabetikumok, vérnyomáscsökkentők, antiepileptikumok és antipszichotikumok. Az elmúlt néhány évtizedben számos közlemény jelent meg a fenti szerek, különösen az acetazolamid általános alkalmazása mellett, idioszinkráziás hatásként jelentkező sugártest-és érhártyaleválás-ról, amit minden publikált esetben tranzitórikus myopia és/vagy akut szemnyomás-emelkedés megjelenése kapcsán diagnosztizáltak [1][2][3][4][5][6][7][8][9][10]. Az utóbbi két tünet megjelenésének a hátterében a sugártest ödémája áll, ami az úgynevezett iris-lencse diaphragma előretolódását, és szükségszerűen az elülső csarnok sekélyebbé válását eredményezi.…”
unclassified
“…Ingestion of sulphonamide-derived drugs has been reported to possibly have ocular side-effects [10][11][12][13][14][15]. Among these drugs are acetazolamide (Diamox) [16][17][18][19][20][21], indapamide [22,23], sulphasalazine [24], methazolamide [25], co- …”
mentioning
confidence: 99%